Plane strain bifurcations of elastic layered structures subject to finite bending: theory versus experiments - Roccabianca, S.; Gei, M.; Bigoni, D. (IMA journal of applied mathematics, 2010)
Finite plane strain bending is solved for a multilayered elastic–incompressible thick plate. This multilayered solution, previously considered only in the case of homogeneity, is in itself interesting and reveals complex stress states such as the existence of more than one neutral axis for certain geometries. The bending solution is employed to investigate possible incremental bifurcations. The analysis reveals that a multilayered structure can behave in a completely different way from the corresponding homogeneous plate. For a thick plate of neo-Hookean material, for instance, the presence of a stiff coating strongly affects the bifurcation critical angle. Experiments designed and performed to substantiate our theoretical findings demonstrate that the theory can be effectively used as a design tool for predicting the capability of an elastic multilayered structure to be subject to a finite bending without suffering localized crazing.